SOSIALISASI DAN PELATIHAN PERHITUNGAN PPH PASAL 21 MENURUT UNDANG-UNDANG NOMOR 7 TAHUN 2021 - Fatimah Nurjannati Iskandar (Adiba Aisha Amira, 2023)
This research aims to examine and socialize the procedure for calculating Income Tax (PPh) Article 21 in accordance with the provisions of Law Number 7 of 2021. By using structured socialization and training methods, this research seeks to increase the understanding and skills of taxpayers, especially perpetrators. small and medium enterprises (SMEs) as well as employees in various sectors, in calculating PPh Article 21 correctly and efficiently.